Jazz. Episode five, Swing, pure pleasure [videorecording (DVD)] - Burns, Ken, 1953-; Marsalis, Wynton, 1961-; Brubeck, Dave; Hampton, Lionel; Levy, Stan (PBS Home Video ; Distributed by Paramount Home Entertainment, 2004)
In the mid 1930s, as the Great Depression refuses to lift, Benny Goodman finds himself hailed as the "King of Swing" and becomes the first white bandleader to hire black musicians. He has a host of rivals among them, Chick Webb, Tommy Dorsey, Jimmie Lunceford, Glen Miller and Artie Shaw. Louis Armstrong heads a big band of his own, while Duke Ellington continues his independent course, but great black artists still can't eat or sleep in many of the hotels where they perform. Billie Holiday emerges from a childhood of tragedy to begin her career as the greatest of all female jazz singers.